Colección del germoplasma de oca del Perú - Nina Montiel, Victor Constantino; Zuñiga Bernal, Mary; Biondi Thorndike, Jorge Andrés; Fernández Huaytalla, Elizabeth; Guerra Arévalo, Luis Enrique; Zorrilla Cisneros, Cinthya; Amasifuen Guerra, Carlos Alberto (Instituto Nacional de Innovación Agraria, 2020)
886 Páginas